Muddy coasts of the world : processes, deposits, and function - Healy, Terry R.; Wang, Ying, 1935-; Healy, Judy-Ann (Proceedings in marine science, 2002)
The SCOR (Scientific Committee on Ocean Research of ICSU) Working Group 106 was tasked with reviewing the geomorphic, sedimentary and oceanographic dynamics of muddy costs, assessing the impact of sea level rise on muddy coasts, especially in estuaries, and to recommend future research pathways relating to muddy coasts. This book addresses these questions and includes chapters on the research issues of muddy coasts, the definition of muddy coasts, sea level rise effects on muddy coasts, fundamental dynamic processes effecting muddy coast formation, the role of mangrove and salt marsh vegetation, bio-geochemistry of muddy coast deposits, storm surge effects on muddy coasts, human impacts on muddy coasts, and a detailed geographical review of muddy coasts of the world. The volume presents examples of muddy coasts sedimentation from many different environments of the world including the broad expanse muddy coast of China, muddy coasts of continental trailing edges (the Americas), muddy coasts in seasonally ice covered environments, muddy coasts in areas of tropical coral reefs, muddy coasts from the tropics, muddy coasts resulting from large river discharges, and muddy coasts of mid-latitude oceanic islands.